Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific) - Sanamyan, K.; Sanamyan, N. (Zootaxa, 2017)
Fifteen species of ascidians were identified in the material collected at Matua Island. Two species are new, Botryllus flavus n. sp. and Distaplia matua n. sp. The first species occurs also at Kamchatka waters, while the second is probably an endemic of Kuril Islands. The genus Macrenteron Redikorzev, 1927 is synonymized with Aplidium Savigny, 1816 and a new name Aplidium macrenteron nom. nov. is proposed for its type species.